Effect of oxygen annealing on the set voltage distribution Ti/MnO 2/Pt resistive switching devices - Choi, S.Y.; Yang, M.K.; Lee, J.-K. (2012)
Significant improvements in the switching voltage distribution are required for the development of unipolar resistive memory devices using MnO x thin films. The V set of the as-grown MnO x film ranged from 1 to 6.2V, whereas the V set of the oxygen-annealed film ranged from 2.3 to 3V. An excess of oxygen in an MnOx film leads to an increase in Mn 4+ content at the MnOx film surface with a subsequent change in the Mn 4+/Mn 3+ ratio at the surface. This was attributed to the change in Mn 4+/Mn 3+ ratios at the MnO x surface and to grain growth. Oxygen annealing is a possible solution for improving the switching voltage distribution of MnO x thin films. In addition, crystalline MnO x can help stabilize the Vset and Vreset distribution in memory switching in a Ti/MnOx/Pt structure. The improved uniformity was attributed not only to the change of the crystallinity but also to the redox reaction at the interface between Ti and MnO x.
Keywords: As-grown; Crystallinities; Effect of oxygen; Film surfaces; Memory switching; MnOx; Oxygen annealing; Resistive memories; Resistive switching; Set voltage; Switching voltages; Voltage distribution; Annealing; Grain growth; Manganese; Oxygen; Platinum; Redox reactions; Switching systems; Thin films; Voltage distribution measurement; Voltage dividers; Manganese oxide